Penghapusan Unsur Merugikan Keuangan Negara: Sinkronisasi Undang-Undang Tipikor dengan UNCAC - Christian Samuel Lodoe Haga; Ade Adhari (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
The current Corruption Law still uses the element of "causing loss to state finances" as the main element of the crime, thus creating legal uncertainty and limiting the effectiveness of corruption eradication. This study uses a normative juridical method with a comparative legal approach between the Corruption Law and the United Nations Convention against Corruption (UNCAC) to analyze the direction of synchronization between the two. The results show that the UNCAC does not require state losses, but rather emphasizes the corrupt act itself, such as abuse of office, bribery, and illicit acquisition of wealth. In conclusion, the removal of this element is an important step in synchronizing the Corruption Law with the UNCAC. Therefore, the recommendation for its removal should focus on unlawful acts and asset recovery.